Depression and inflammation among epidermal growth factor receptor (EGFR) mutant nonsmall cell lung cancer patients. Issue 7 (15th May 2019) - McFarland, Daniel C.; Jutagir, Devika R.; Rosenfeld, Barry; Pirl, William; Miller, Andrew H.; Breitbart, William; Nelson, Christian
Abstract: Objective: Depression is highly prevalent in nonsmall cell lung cancer (NSCLC) and is associated with elevated inflammation. However, certain subtypes of driver mutation–associated NSCLC such as epidermal growth factor receptor (EGFR)–mutated NSCLC may be associated with less depression given the differences in their underlying biology and disease trajectories. Biological variables such as inflammation, measured by C‐reactive protein (CRP), may provide insight into depression variability in EGFR mutant NSCLC. Methods: Patients with EGFR mutant and wild‐type metastatic NSCLC were evaluated for depression using the Hospital Anxiety and Depression Scale (HADS) on a continuous scale and meeting depression screening criteria (HADS ≥ 8). Inflammation was measured using CRP. A mediation model was created to understand how inflammation mediates EGFR wild‐type associated depression. Results: One hundred out of 120 patients with NSCLC were recruited (83.3% response rate). The 20 participants with EGFR mutant NSCLC had less depression (HADS‐D 3.0 versus 5.4) ( P  < .001), met depression screening criteria less often ( P  = .047), and exhibited less inflammation (CRP = 0.23 mg/mL versus 2.71 mg/mL) ( P  < .001) in comparison with EGFR wild‐type NSCLC. Multivariate linear regression model revealed that only CRP predicted depression ( P  = .015) while controlling for age and sex. Mediation analysis found that lower CRP partially mediated less depression in EGFR mutant NSCLC. Conclusions: EGFR mutant NSCLC is associated with less depression but the relationship is partially mediated by lower CRP‐related inflammation, which is a stronger predictor of depression than EGFR status. Depression in lung cancer varies by subtype and is significantly related to inflammation.